Analisis Transmisi Saluran Suku Bunga dan Harga Aset pada Penerapan Flexible ITF di Indonesia - Taufiq Hidayat; Nugroho Sumarjiyanto Benedictus Maria (Diponegoro Journal of Economics, 2023)
This study aims to analyze the effectiveness of monetary policy transmission implemented by Bank Indonesia through the interest rate and asset price channels in achieving the final target, inflation. The method used in this study is the Vector Error Correction (VEC) model, and the data utilized are monthly data from August 2016 to December 2022. The VEC model shows that, in the long term, the transmission of monetary policy through the interest rate and asset price channels proves to influence inflation. However, in the short term, only the asset price channel shows a significant effect on inflation. The originality of this research lies in analyzing the use of the BI-7 DRR as the new benchmark interest rate in the implementation of the Flexible ITF.